A Comparative Study of Ductile Damage Models Approaches for Joint Strength Prediction in Hot Shear Joining Process. (2017) - Murugesan, Mohanraj; Lee, Seonggi; Kim, Dongwook; Kang, Youn-Hee; Kim, Naksoo
Abstract: Ductile fracture prediction is often considered as a challenging task in complex stress state applications, such as metal joining process. A systematic method for predicting the joint strength in the hot shear joining process is presented in this paper by considering two different ductile damage models, namely Johnson-Cook and modified Lemaitre damage models. Since the crack formation in metalworking is considered to be a combination of both load conditions and metallurgical properties, the microstructure evolution is taken into account by characterizing the considered material, AISI-1045, at different temperatures and for different strain rates and by testing different specimen shapes, namely round bar, joint bar, flat and notched specimens. The derived material properties have been inversely calibrated in order to be used in the developed numerical model. A shear joining process simulation has been implemented in DEFORM and have been validate with shear joining experiments carried out at 950°C, allowing to validate the accuracy of the proposed model in simulating the hot shear joining, both in terms of joining strength and identification of the damage locations. Thanks to a precise material characterization, and by utilizing the proposed numerical model, both the joining tool design and the process condition can be studied and improved.